Profile of Student Learning Outcomes on the Concept of Sorting Numbers with a Realistic Mathematcs Education - Omas Tuankotta; La Suha Ishabu; Rosmaryn Tutupary (Lembaga Intelektual Muda (LIM) Maluku, 2020)
This study aims to determine the profile of student learning outcomes on the concept of sequencing numbers with a Realistic Mathematics Education in grade I SD Muhammadiyah Ambon. The type of research used in this study is Descriptive Quantitative, which is research that aims to obtain data and describe the profile of student learning outcomes. The subjects of this study were all grade I students of SD Muhammadiyah Ambon, totaling 30 people. The variable used in this study is a single variable, namely the profile of student learning outcomes. The instruments used in data collection are test questions and observation guidelines. Data analysis is carried out descriptively, namely calculating the average score and percentage of completion of learning students. The results of the analysis show that it can be concluded that, on average, learning outcomes using the Realistic Mathematics Education achieved quite maximum student learning outcomes. Based on the results of the analysis of students' initial test scores, the average score was 58.33 with a percentage of completion as much as (26.67%) and increased in the final test results to 88.33 with a complete percentage of 93.33%. The number of students who achieved a minimum completion score on the initial test amounted to 8 students and increased in the final test by 28 students